Impactos socioambientais da atividade mineradora no município de Brumado – BA - Moreira, Poliana Machado da Silva (2020)
Today's society has reached a high level of modernization, characterized by the evolution of information, the production of wealth and the creation of new technologies, or which has enabled better living conditions for man. On the other hand, it manifests itself in deep environmental crises related to the indiscriminate use of natural resources and socioenvironmental impact variables. Other activities performed by man in changing the natural environment, mining is reduced. An important and necessary industrial activity, although modified in the environment, often associated with social issues, involves conflicts of land use and generation of degraded areas, which are generated by the lack of interventions that recognize the plurality of interests involved. This research has as study place the municipality of Brumado located in the southwest of Bahia, 550 km from Salvador. The geo economic organization of mineral production in Brumado is used to insert non-metallic minerals into the country's economic scenario. Since the implantation of mining companies, the municipality has become an exponent in mineral exploration, or has brought a new social space community. In this context, the thesis is conceived that mining in the municipality of Brumado has made the population dependent, inhibits the development of other economic activities, and that mining activity generates socio-environmental impacts, guided by the general objective of understanding how mining activity has been producing new territorialities. The method chosen for the interpretation of the problem is the structuralist and the methodological procedures for the analysis were theoretical and documentary survey, interviews, application of a semistructured questionnaire, field diary and mapping. The results show that the population and the local government, due to the mining discourse generated by development, see mining activity as an opportunity for economic development and social growth, failing to promote other activities. In reality or where it is observed that specialized services are brought from other locations, the restoration of jobs formed by outsourced companies, subordinated to precarious working conditions, the performance of functions such as security, cleaning and maintenance services and, therefore, the development not carried out, therefore, the municipality is unable to establish as bases for this to happen. There are no more expressive conflicts between the population and mining companies, the impasses between them are related to the precarious conditions of labor exploitation, the diseases caused by inhalation of dust from mining and the defense of territories. Although the mining activity promotes the circulation of capital and the movement of the economy in the place where it is installed, the large mining enterprises have interests that differ from those of a large part of the population.